The Nutritional Potential of Ari Soybean Hulls as an Alternative Feed Ingredient Poultry: A Literature Review - Risdawati Ginting; Meriksa Sembiring; Sri Setyaningrum; Puteri Wahyu Lestari (Yayasan Sinergi Multidimensi Kreatif, 2024)
Soybean hulls are agro-industrial waste from soybean processing, especially in the tofu and tempeh industries. This waste is often ignored and has not been optimally utilized, even though it has potential as a feed ingredient for poultry. This article aims to assess the nutritional potential of soybean hulls and its feasibility as an alternative ingredient in poultry feed. Based on the results of a literature study, soybean hulls contain crude fiber, protein, and a number of minerals that are important for poultry growth, although the crude fiber content is quite high which can limit digestibility. Several processing techniques such as fermentation and chemical treatment can increase its nutritional value. With proper processing, soybean hulls have great potential to be an economical and environmentally friendly alternative feed ingredient.